HOMESTAY START-UP MODELTO SUPPORT SUSTAINABLE TOURISM IN LOMBOK, INDONESIA - Akhmad Saufi; Baiq Handayani Rinuastuti; Agusdin Agusdin; Lalu M. Furkan (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2019)
Despite the important roleof local entrepreneurs for sustainable tourism, the process of starting up small tourism enterprises remains unclear. The current study is aimed at constructing a start-up model of small tourism enteprise, particularly homestay.Qualitative method was adopted. Data was collected using semi-structured interviews, observation, and documentary. Interviews were made with 6 homestay owners in three tourist destinations in West Lombok Regency. Data was recorded and then analysed using content analysis. The study constructs a start-up model consisting of two phases, orientation and starting phases. The orientation phase elaborates the process of entrepreneurial opportunity recognition, business capital preparation, and  starting preparation. The starting phase describestrial and error process regarding product creation, resource allocations, finance management, and marketing strategies. In the starting phase entrepreneurs have todeal with business competition and business uncertainties. The succes in undertaking the starting phase can lead an entrepreneur into a further business development. But,the fail in going through the starting phase can lead into bankruptcy and/or the situation in which the entrepreneurs have to re-start their business again from the beginning. The study results provide reference for community empowerment, bring theoretical and managerial impacts, and create gap for a further research. Keywords : homestay start-up, orientation phase, starting phase, tourism industry, Lombok